2005
DOI: 10.1002/jssc.200500116
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional separation of peptides using RP‐RP‐HPLC system with different pH in first and second separation dimensions

Abstract: Two-dimensional high performance liquid chromatography is a useful tool for proteome analysis, providing a greater peak capacity than single-dimensional LC. The most popular 2D-HPLC approach used today for proteomic research combines strong cation exchange and reversed-phase HPLC. We have evaluated an alternative mode for 2D-HPLC of peptides, employing reversed-phase columns in both separation dimensions. The orthogonality of 2D separation was investigated for selected types of RP stationary phases, ion-pairin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
368
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(376 citation statements)
references
References 37 publications
3
368
0
2
Order By: Relevance
“…In recent years, a different 2D-LC methodology has been developed, based on the RP separation under basic pH (pH 10) conditions in the first dimension and a low-pH RP separation in the second dimension. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] In all reported work using capillary chromatography (e.g., 300 μm ID columns), [26][27][28][29][30][31][32][33][34][35][36] the first LC dimension was operated in an off-line mode using fraction collection, followed by excess organic solvent evaporation mAbs Fig. 2B) from the second dimension (lowpH) separations in four consecutive injections (experiments).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a different 2D-LC methodology has been developed, based on the RP separation under basic pH (pH 10) conditions in the first dimension and a low-pH RP separation in the second dimension. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] In all reported work using capillary chromatography (e.g., 300 μm ID columns), [26][27][28][29][30][31][32][33][34][35][36] the first LC dimension was operated in an off-line mode using fraction collection, followed by excess organic solvent evaporation mAbs Fig. 2B) from the second dimension (lowpH) separations in four consecutive injections (experiments).…”
Section: Resultsmentioning
confidence: 99%
“…The method used two-dimensional liquid chromatography in a high-low pH reversed phase/reversed phase configuration on a nanoACQUITY UltraPerformance liquid chromatography system coupled to a Synapt G2 High Definition Mass Spectrometer (both Waters Corporation) with nanoelectrospray ionization as similarly described previously (35)(36)(37). Peptides were first trapped at 2 l/min at 97/3 v/v 20 mM ammonium formate in water, pH 10/acetonitrile on a 5 m XBridge BEH130 C18 300 m ϫ 50 mm column (Waters Corporation).…”
Section: Methodsmentioning
confidence: 99%
“…2,3 But, as has been shown in a recent study, other HPLC modes could also be considered: for example, Gilar et al showed that the combination of two RP-HPLC separations, if performed at two significantly different pHs (2.6 and 10.0), can be an interesting two-dimensional separation method with rather orthogonal separation principles. 4 Although chromatographic techniques are widely used, it has already been shown that capillary electrophoresis (CE) can represent a very interesting alternative. Indeed, in comparison to HPLC, CE provides higher efficiencies and separation speeds.…”
mentioning
confidence: 99%
“…The tryptic digest of a four-protein mixture has been considered as a test sample. IEF fractionation by OGE has been performed on a wide pH range (3)(4)(5)(6)(7)(8)(9)(10), and different experimental conditions to perform CE have been tested. Also, to know whether CZE can really be considered as a method complementary to OGE, some significant OGE fractions have also been analyzed by RP-HPLC.…”
mentioning
confidence: 99%